Credit safety net of VietNamese Commercial Banks,Graduation Thesis - Ngo Ngoc Tram,Nguyen Thi Hong Mai
Credit safety net of VietNamese Commercial Banks : Graduation Thesis / Ngo Ngoc Tram; Nguyen Thi Hong Mai supervisor .- H. : Banking Academy , 2014 .- 63 p. ; 28 cm